Study of Clinical Profile in Nontraumatic Adult Patients with Altered Sensorium and Its Correlation with The Outcome at Emergency Room of a Tertiary Care Hospital, Devdaha, Rupandehi - Gaira, Manoj; Darlami, Babita laxmi; Chettri, Sahas; Pandey, Usha Kiran; Koirala, Diwakar (Medical Journal of Eastern Nepal, 2026)
BackgroundAltered sensorium accounts for approximately 4–10% of all emergency visit presentations worldwide, posing a major challenge to emergency doctors. At Devdaha Medical College and Research Institute (DMCRI), 115 non-traumatic adult cases were studied. Early clinical assessment helps timely management and predicts outcomes.Objectives This study aimed to assess the clinical profile and outcome assessment (mortality, morbidity) of non-traumatic patient of altered sensorium.Methods This prospective observational hospital-based study was conducted in the emergency department of DMCRI from April to September 2025. Adult patients (≥18 years) with non-traumatic altered sensorium were included. Data were collected using questionnaire, analyzed using descriptive statistics, including frequency, percentage, and range. Convenience sampling was used after ethical approval (Reference No: 1924/o81/082).ResultsIn 115 patients (age 18–83 years), 64 (55.6%) were male. Most patients (n = 33, 28.6%) were aged 61–70 years. Common presenting complaints were headache (77.3%), nausea / vomiting (70.4%) and focal neurological deficit (61.7%). Cerebrovascular accident (CVA) was the commonest cause (n = 38, 33%), followed by metabolic disorders (n = 29, 25.2%) and substance-related intoxication (n = 24, 20.9%). Overall mortality was 20% (n = 23); mortality was highest among metabolic causes (47.8% of deaths), followed by CVA (21.7%) and substance poisoning (13%). At discharge, 48 (41.7%) patients had complete recovery and 44 (38.2%) had residual disability.ConclusionsAltered sensorium predominantly affected elderly patients, with stroke and metabolic disturbances. Early recognition helps to reduce poor outcome. Strengthening emergency and inpatient care can significantly improve outcomes.